Environmentally Friendly Maltodextrin-Chitosan Encapsulation in Cocoa Husk Extract (Theobroma cacao Linn.) for Corrosion Inhibition on Steel in Corrosive Media - Gusti, Diah Riski; Toyyibah, Fida; Nizori, Addion; Restianingsih, Tika; Faiquzzaky, Faiz; Tajuddin, Nazrizawati Ahmad (Chempublish Journal, 2026)
This research tested an encapsulated cocoa husk extract formulated with maltodextrin and chitosan at an 8:2 ratio for use as a steel corrosion inhibitor. The method of weight loss in 0.75 M sulfuric acid, seawater, and peat water solutions was used to test inhibitors. The analysis indicated that inhibitor efficiency increased with increasing concentration. At the same time, its efficiency decreased due to longer immersion periods, reaching a maximum of 94.07% in peat water when a 2.5 g/L concentration of inhibitors was applied for 1 day. These results indicate significant potential for encapsulated cocoa husk extract as a natural corrosion inhibitor